Liberation and democratization : the South African and Palestinian national movements - Younis, Mona (Social movements, protest, and contention, 2000)
Arising in the 1910s and emerging as legitimate governing bodies in the 1990s, the South African and the Palestinian national liberation movements have exhibited remarkable parallels over the course of their development. The fortunes of the African National Congress and the Palestinian Liberation Organization, however, have proven strikingly different. How the movements, despite similar circumstances and experiences, have arrived at such dissimilar outcomes is described in Liberation and Democratization.